Fatty acid, cholesterol and fat-soluble vitamin composition of wild and captive freshwater crayfish (Astacus leptodactylus) - Harlioglu, A. Gul; Aydin, S.; Yilmaz, O. (Sage Publications Ltd, 2012)
The proximate analysis (dry matter, protein, fat and ash), cholesterol, fatty acid and fat-soluble vitamin compositions of the tail muscle of wild caught and captive crayfish (Astacus leptodactylus) were investigated. Captive crayfish contained higher moisture and fat content than wild crayfish. In contrast, wild crayfish contained a higher level of crude protein, ash and n-3 polyunsaturated fatty acids (PUFA), particularly eicosapentaenoic (EPA) and docosahexaenoic acid (DHA) than captive crayfish. Arachidonic acid (C20:4 n-6) was the major n-6 PUFA in wild A. leptodactylus, and linoleic acid (C18:2 n-6) was the major n-6 PUFA in captive A. leptodactylus. The percentages of total saturated fatty acids (SFA), PUFA, and n-3/n-6 ratio were higher in wild crayfish and total monounsaturated fatty acids (MUFA) were lower. Although differences existed between wild and captive crayfish in vitamins A (p < 0.001), delta-Tocopherol (p < 0.001), alpha-Tocopherol acetate (p < 0.05), no differences were found in vitamins D-2, D-3, alpha- Tocopherol and K (p > 0.05). The differences may be originated from the diet provided to captive crayfish. Since wild A. leptodactylus contained higher n-3/n-6 ratio than captive A. leptodactylus, crayfish farms can potentially produce a better quality of crayfish meat by increasing the PUFA n-3 (especially DHA and EPA) in the diets of A. leptodactylus.
Keywords: Astacus leptodactylus; cholesterol; fat-soluble vitamin; fatty acids